2014
DOI: 10.1039/c3ob42586j
|View full text |Cite
|
Sign up to set email alerts
|

Non-stoichiometric O-acetylation of Shigella flexneri 2a O-specific polysaccharide: synthesis and antigenicity

Abstract: Synthetic functional mimics of the O-antigen from Shigella flexneri 2a are seen as promising vaccine components against endemic shigellosis. Herein, the influence of the polysaccharide non-stoichiometric di-O-acetylation on antigenicity is addressed for the first time. Three decasaccharides, representing relevant internal mono- and di-O-acetylation profiles of the O-antigen, were synthesized from a pivotal protected decasaccharide designed to tailor late stage site-selective O-acetylation. The latter was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 85 publications
4
37
0
Order By: Relevance
“…In contrast, other investigations have concluded that O‐acetylation was not essential for protective mAb binding to the SF2a O‐Ag, which is acetylated in a non‐stoichiometric fashion at the OH‐3 A and OH‐6 D groups, the later being shared with the SF3a O‐Ag . Instead, the glucosyl side chain, in this case present within an (E)C branch (α‐ d ‐Glc p ‐(1→4)‐α‐ l ‐Rha p ) as part of the B(E)CD segment, was demonstrated to be critical for binding to five independent protective mIgG .…”
Section: Resultsmentioning
confidence: 73%
“…In contrast, other investigations have concluded that O‐acetylation was not essential for protective mAb binding to the SF2a O‐Ag, which is acetylated in a non‐stoichiometric fashion at the OH‐3 A and OH‐6 D groups, the later being shared with the SF3a O‐Ag . Instead, the glucosyl side chain, in this case present within an (E)C branch (α‐ d ‐Glc p ‐(1→4)‐α‐ l ‐Rha p ) as part of the B(E)CD segment, was demonstrated to be critical for binding to five independent protective mIgG .…”
Section: Resultsmentioning
confidence: 73%
“…the Generalized Modules for Membrane Antigens (GMMA) approach [ 5 , 6 ]], as well as to improve the immunogenicity of the existing antigens (e.g. synthetic chemistry for glycoconjugates [ 7 ]). To this end, partners of the STOPENTERICS consortium have been integrating basic research, particularly genomics, transcriptomics, proteomics, and other high-throughput technologies, with novel vaccine technologies and synthetic chemistry [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…synthetic chemistry for glycoconjugates [ 7 ]). To this end, partners of the STOPENTERICS consortium have been integrating basic research, particularly genomics, transcriptomics, proteomics, and other high-throughput technologies, with novel vaccine technologies and synthetic chemistry [ 7 ]. To assemble Shigella expertise to identify and rapidly take novel vaccine candidates through to clinical trials for effective vaccine development, the research is carried out among different academic institutions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…2, the target oligosaccharides would come from five suitably functionalized talose donors ( 8 – 12 ), which are activated at their anomeric position with a trichloroacetimidate (TCA) group 48 . The choice of the TCA group was motivated by the high-yielding coupling reported for structurally similar l -rhamnose donors in the context of the synthesis of bacterial glycans 49 . All of these donors ( 8 – 12 ) were synthesized using a C4 oxidation/reduction sequence from a common allylated rhamnose precursor followed by subsequent regioselective 3-O-methylation or 3-O- para -methoxybenzylation via optimization of the stannylene acetal chemistry 50 (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%